Pengembangan Sistem Penjualan Toko Latansa Textile berbasis Web - Muhammad Miftah Dhiaulhaq; Edy Santoso; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Latansa Textile is one of the textile shops established in Balikpapan, East Kalimantan. The shop manages its sales transaction as a business report with a manual book and hand-writing. Hence, the transaction notes might be piled up. Delay of re-stock also occurred since the shop has never recorded the material stock, and it causes failure to comply with textile buyers' demand. To overcome the problem, a web-based sales system was developed to facilitate the process of transaction management. Object-Oriented Analysis and Design and Object-Oriented Programming methods were employed to develop the system. It was developed with Hypertext Preprocessor (PHP) as the programming language and Codeigniter as the framework. Unit testing and integration testing employed the white-box method, while validation testing employed the black-box method. Results of the unit testing and integration testing show that the system runs as designed. The result of validation testing shows that the system fulfills all the functional requirements. Thus, all the testing show 100% validity, and the system is ready to use.